RESULTS OF MASS SCREENING OF NEWBORNS WITH CYSTIC FIBROSIS IN MOSCOW - Z.A. Kusova; N.V. Petrova; T.A. Vasil'eva; N.Yu. Kashirskaya; R.A. Zinchenko; N.I. Kapranov ("Paediatrician" Publishers LLC, 2010)
Neonatal screening of cystic fibrosis is able to provide early presymptomatic diagnosis of the disease in newborns. The objective of this study was to evaluate an effectiveness of neonatal cystic fibrosis screening in Moscow. Authors studied molecular-genetical samples of DNA in 1,260 newborns with hypertripsinogenemia (the level of immunoreactive tripsin in first test - IRT I was > 70 ng/ml) for the presence of most frequent mutations of gene CFTR. All children were born in Moscow in 2008. They formed risk group because of results of IRT I test. Mutations were detected in 53 persons (47 heterozygotes and 6 homozygotes). The rate of false-negative results was 0.16 %; the result was similar to European data.Key words: newborns, neonatal screening, cystic fibrosis, hypertripsinogenemia, CFTR gene, mutations.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(6):26-30)